(untitled) (African Sociological Review, 2021)
Contents Editorial 1: Invitation: Contribution to Special Issue on COVID-19 in Africa General Issue Covid-19, Crise de Souveraineté et Persistance de la Colonialité: Politico-économique en Afrique Noire Jacquineau Azétsop & Ghislain Abéga ........................................6 Individuals, Conglomerates, Persons, and Communities Gertjan van Stam ..........................................................32 Research Papers Ethnicity as an Independent variable in African Politics. Lessons learned from the 2017 Kenya Presidential Elections Paul Tang Abomo .............................................................................48 Aetiological Explanations of Epilepsy and Implications on Treatments Options among Yoruba Traditional Healers in Southwest Nigeria Tosin Funmi Ademilokun & Ojo Melvin Agunbiade ..................................86 Le travail domestoque : occulation de la catégories de genre existance Melchicedec Nduwayezu, Salvator Nahimana & Célestin Mvutsebanka .........................112 Government-driven land and Agrarian Reform Programmes in Post-Apartheid South Africa – a Brief History (1994-2019) Roland Nkwain Ngam ............................................................131 Fonds miniers volontaires et développement communautaire au Sénégal : quelle place et quels rôles pour la démocratie délibérative et participative ? Bakary Doucouré .......................................................................153 Homeownership Intention among Igbo Ethnic Group in Ilorin Olusegun F. Liadi & Aisha Sanusi Tapamose ......................................169 Reflection on student drop-out against the backdrop of COVID-19 in the South African Educational context amongst marginalised groups of students Peggy Pinky Mthalane, Albert Tchey Agbenyegah & Bongani Innocent Dlamini ...............................194 Lessons from an ethnographic encounter with young women in a South African Township Sinethemba S. Sidloyi ......................218